2018
DOI: 10.1177/1557988318801655
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Likelihood of Seeking Social Worker Help Among Older Men in Israel

Abstract: The current study assessed the association between demographic factors (age, relationship status, and education), psychosocial factors (self-rated health and self-reported loneliness), and factors related to attitudes and behaviors associated with seeking help (prior experience with social workers, attitudes towards social workers, and the stigma attached to seeking help from social workers, and the self-reported likelihood of seeking social workers’ help among older men in Israel. The data were collected thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…In regards to accessibility and awareness of formal services, older adults expressed related issues such as costs, long wait times, short consultation times or having busy schedules as help-seeking barriers (Djukanović et al, 2015; Dollard et al, 2014; Frost et al, 2020; Garg et al, 2017; Garrido et al, 2011; Hannaford et al, 2019; Kagan et al, 2018; Lawrence et al, 2006; Lee et al, 2012, 2020; Murata et al, 2010; Polacsek et al, 2019; Schneider et al, 2014; Waterworth et al, 2018). Location and lack of available transportation also made it more difficult for older adults to seek help, especially among those living in rural areas or those with physical constraints (Chen, 2020; Chung et al, 2018; Frost et al, 2020; Garg et al, 2017; Garrido et al, 2011; Gur-Yaish et al, 2016; Mukherjee, 2019; Murata et al, 2010; Polacsek et al, 2019; Waterworth et al, 2018).…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…In regards to accessibility and awareness of formal services, older adults expressed related issues such as costs, long wait times, short consultation times or having busy schedules as help-seeking barriers (Djukanović et al, 2015; Dollard et al, 2014; Frost et al, 2020; Garg et al, 2017; Garrido et al, 2011; Hannaford et al, 2019; Kagan et al, 2018; Lawrence et al, 2006; Lee et al, 2012, 2020; Murata et al, 2010; Polacsek et al, 2019; Schneider et al, 2014; Waterworth et al, 2018). Location and lack of available transportation also made it more difficult for older adults to seek help, especially among those living in rural areas or those with physical constraints (Chen, 2020; Chung et al, 2018; Frost et al, 2020; Garg et al, 2017; Garrido et al, 2011; Gur-Yaish et al, 2016; Mukherjee, 2019; Murata et al, 2010; Polacsek et al, 2019; Waterworth et al, 2018).…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…At the same time, during the COVID-19 pandemic, it became more prevalent and intensive following the government's instructions for minimizing the spread of the virus, which included social isolation, working from home, limiting social ties, and lockdowns ( CBS, 2020 ; WHO, 2020 , 2021 ). However, the association between loneliness and seeking help from SWs has received fairly limited research attention ( Kagan et al, 2018 ) and to the best of our knowledge has yet to be investigated during the COVID-19 crisis, when loneliness became more prevalent ( CBS, 2020 ; Kovshi-Eldan & Bing, 2020 ). Studies on this issue in the period preceding the COVID-19 pandemic indicate that lonely people are more likely to seek help from helping professionals and particularly SWs ( Auslander et al, 2003 ; Kagan et al, 2018 ) since in the absence of sufficient personal and social resources they might have more need of professional help and support.…”
Section: The Contribution Of Psycho-social Variables To Explaining Th...mentioning
confidence: 99%
“…Studies conducted on this subject in Israel, where the current study was carried out, show that fairly high proportions of the respondents reported a very low likelihood, or no likelihood at all, of seeking help from SWs. For instance, in two studies among the general population in Israel ( Kagan & Zychlinski, 2016 , 2017 ), such statements were made by 37.7% and 32.1% of the respondents, respectively, while among people with physical disabilities the proportion was 35% ( Kagan et al, 2017 ) and among older men 39% ( Kagan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations